Spot-billed toucanet Selenidera maculirostris (Aves: Ramphastidae): importance of citizen science and scientific data in investigating its occurrence in modified environments around the largest urban area in South America - Schunck, Fabio; Rodrigues, Maria Luciene da Silva; Rego, Marco Antonio (Frontiers in Bird Science, 2025)
Toucans and toucanets are widely distributed in the Neotropical Region. Some species perform regional movements in search of food resources, but little is known about this behavior and the use of modified habitats. The spot-billed toucanet Selenidera maculirostris is endemic to the Atlantic Forest of Brazil, Paraguay, and Argentina. The species is threatened with extinction in the state of São Paulo (Brazil) due to deforestation. We compiled historical and current data on the occurrence of the species in the São Paulo Metropolitan Region (SPMR), the largest urban area in South America, to investigate the hypothesis that this species performs seasonal regional movements between preserved forests and modified areas during the autumn and winter. Data from the literature, online platforms, and a 17-year field study produced a total of 200 records since 1889, for 45 locations, indicating that the species has a wide occurrence in the SPMR, being common to the Serra do Mar. It occurs in the preserved forests of the southern portion of the SPMR throughout the year and is more common in the altered and fragmented forests near the Serra do Mar in autumn–winter. These possible seasonal movements between more preserved areas and altered areas are probably in search of food, a behavior that needs further study since the forests of the SPMR have been rapidly destroyed in recent years.